Tb3+-Doped Ag-MOFs for fluorescent detection of formaldehyde in a novel smartphone platform and its removal applications in milk products and wastewater. Issue 54 (22nd October 2021) - Li, Mengwen; Shen, Ao; Du, Man; Hao, Xiaohui; Wang, Hongquan; Du, Xiaoyu; Ma, Shufeng; Yuan, Jiaxin; Yang, Yunxu
Abstract : Tb 3+ -Doped Ag-MOFs for fluorescent detection of formaldehyde in a novel smartphone platform and their removal applications in milk products and wastewater. Abstract : As one kind of reactive carbonyl species (RCS), formaldehyde (FA) with a high concentration could be extremely toxic to living bodies as well as the environment. This paper reports a three-dimensional (3D) Tb 3+ @Ag-MOFs-based fluorescent probe for fast sensing of FA, which uses a novel turn-on mechanism based on the luminescence induced by Tb 3+ . The MOF sensor shows broad dynamic ranges of 0.1–1 mM for FA with the detection limit of 1.9 μM. For online and real-time detection of FA, a portable smartphone platform was employed to analyze the RGB values of the fluorescence by a smartphone application. By incorporating this probe into a polyacrylonitrile (PAN) layer, we synthesized a film composite that could effectively remove FA in real samples including milk and chemical factory wastewater, and the removal rate reached 98.52% and 95.38% respectively. Moreover, the potential of the film to remove gaseous FA was confirmed by experiments as well.